Efficient DNA condensation by ruthenium(ii) polypyridyl complexes containing triptycenyl functionalized 1, 10-phenanthroline. (2nd June 2017) - Bhat, Satish S.; Revankar, Vidyanand K.; Pinjari, Rahul V.; S, Naveen; Bogar, Chetana; Bhat, Kishor; Kawade, Vitthal A.
Abstract : A series of luminescent ruthenium(ii ) polypyridyl complexes containing an extended aromatic moiety derived from triptycene and 1, 10-phenanthroline were synthesized and their photophysical, theoretical, and biological properties were investigated. Abstract : A series of luminescent ruthenium(ii ) polypyridyl complexes containing an extended aromatic moiety derived from triptycene and 1, 10-phenanthroline were synthesized and their photophysical, theoretical, and biological properties were investigated. These complexes rapidly condense DNA into nano-aggregates at room temperature. The DNA interactions and DNA condensation properties of these complexes were investigated by absorption and emission spectroscopy, electrophoretic mobility assay, and atomic force microscopy. Their DNA cleavage inactivity and low toxicity of the complexes satisfy the requirements of a good non-viral gene delivery vector.